PENGEMBANGAN MEDIA PAPAN FLANEL UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK DI MI/SD - Asrin Nasution; Aninditya Sri Nugraheni (Jurnal Al-Fatih, 2021)
The urgency of educational media as assistive equipment in delivering educational modules is also on the flannel board media which aims to improve students' conceptual descriptions in mastering the water cycle module lessons. The results of the research and development that were tried shared an explanation that: the Flannel Board Media product that has been raised is "very feasible" to be used after passing the validation test from learning media experts with a percentage value of 97.5% and education module experts with a percentage value of 100%, after that seen from the results of practicality testing through product trials in the main field by the teacher, the percentage value was obtained 100% and students obtained a percentage value of 85.56% so that "very instant" was used like an educational medium and "efficient" was used in education. Flannel Board media is valid, instant and efficient to improve students' conceptual descriptions in the Water Cycle module.